The association between physician trust and prostate-specific antigen screening: Implications for shared decision-making - Klaassen, Zachary; Wallis, Christopher J.D.; Goldberg, Hanan; Chandrasekar, Thenappan; Fleshner, Neil E.; Finelli, Antonio; Kulkarni, Girish S.; Detsky, Allan S.; Satkunasivam, Raj (Canadian Urological Association Journal, 2018)
Introduction: Shared decision-making is widely recommended when men are considering prostate cancer screening with prostatespecific antigen (PSA). The role of patients’ trust in cancer information from their physician in such decisions is unknown. Methods: We identified male respondents ≥18 years of age from the Health Information National Trends Survey, a population-based survey of people living in the U.S. (2011–014). We assessed the association between degree of trust in cancer information from respondent’s physician with patient-reported receipt of PSA screening and patient-reported discussion of PSA screening with their physician. Results: Among 5069 eligible respondents, 3606 (71.1%) men reported trusting cancer information from their physician “a lot,” 1186 (23.4%) “somewhat,” 219 (4.3%) “a little,” and 58 (1.1%) “not at all.” A total of 2655 (52.4%) men reported receiving PSA screening. The degree of trust an individual had in his physician for cancer information was strongly associated with his likelihood of having received PSA screening (ptrend<0.0001) (54.9% “a lot” vs. 27.6% “not at all”). These findings persisted after multivariable regression. Similarly, men who had high levels of trust in their physician were more likely to have discussed PSA screening with a strong trend across strata (ptrend<0.0001). Conclusions: The level of trust an individual has in cancer information from his physician is strongly associated with his likelihood of discussing and undergoing PSA screening. As rationale, implementation of PSA screening requires shared decision-making, and the level of trust an individual has in his physician has important implications for dissemination of PSA screening guidelines.